Computational analysis of the AP2/ERF family in crops genome - Shouhartha Choudhury (BMC Genomics, 2024)
Abstract Background The Apetala 2/ethylene-responsive factor family has diverse functions that enhance development and torment resistance in the plant genome. In variation, the ethylene-responsive factor (ERF) family of TF’s genes is extensive in the crop genome. Generally, the plant-specific ethylene-responsive factor family may divided by the dehydration-responsive element-binding (DREB) subfamily. So, the AP2/ERF super-family demonstrated the repeated AP2 domain during growth. The sole AP2 domain function represents abiotic stress resistance. Also, the AP2 with B3 domain enhances during the replication of brassinosteroid. Objective The study objective is to investigate the Apetala 2/ethylene-responsive factor family in a model organism of the Arabidopsis thaliana for comparative analysis towards Solanum lycopersicum (Tomato), Brassica juncea (Indian and Chinese mustard), Zea mays L. (Maize) and Oryza sativa (Indian and Japanese Rice). So, examinations of the large AP2/ERF super-family are mandatory to explore the Apetala 2 (AP2) family, ERF family, DREB subfamily, and RAV family involved during growth and abiotic stress stimuli in crops. Methods Therefore, perform bioinformatics and computational methods to the current knowledge of the Apetala 2/ethylene-responsive factor family and their subfamilies in the crop genome. This method may be valuable for functional analysis of particular genes and their families in the plant genome. Results Observation data provided evidence of the Apetala 2/ethylene-responsive factor (AP2/ERF) super-family and their sub-family present in Arabidopsis thaliana (Dicots) and compared with Solanum lycopersicum (Dicots), Brassica juncea (Dicots), Zea mays L. (Monocots) and Oryza sativa (Monocots). Also, remarks genes in Oryza sativa. This report upgraded the Apetala 2/ethylene-responsive factor (AP2/ERF) family in the crop genome. So, the analysis documented the conserved domain, motifs, and phylogenetic tree towards Dicots and Monocots species. Those outcomes will be valuable for future studies of the defensive Apetala 2/ethylene-responsive factor family in crops. Conclusion Therefore, the study concluded that the several species-specific TF genes in the Apetala 2/ethylene-responsive factor (AP2/ERF) family in Arabidopsis thaliana and compared with crop-species of Solanum lycopersicum, Brassica juncea, Zea mays L. and Oryza sativa. Those plant-specific genes regulate during growth and abiotic stress control in plants.